The genus Scrophularia: a source of iridoids and terpenoids with a diverse biological activity - Ardalan Pasdaran; Azadeh Hamedi (Taylor & Francis Group, 2017)
Context: Scrophularia genus (Scrophulariaceae) includes about 350 species commonly known as figwort. Many species of this genus grow wild in nature and have not been cultivated yet. However, some species are in danger of extinction. Objective: This paper reviews the chemical compounds, biological activities and the ethnopharmacology of some Scrophularia species. Materials and methods: All information was obtained through reported data on bibliographic database such as Scopus, United States National Agricultural Library, Biological Abstracts, EMBASE, PubMed, MedlinePlus, PubChem and Springer Link (1934-2017). The information in different Pharmacopoeias on this genus was also gathered from 1957 to 2007. Results: The structures of 204 compounds and their biological activity were presented in the manuscript: glycoside esters, iridoid glycosides and triterpenoids are the most common compounds in this genus. Among them, scropolioside like iridoids have shown potential for anti-inflammatory, hepatoprotective and wound healing activity. Among the less frequently isolated compounds, resin glycosides such as crypthophilic acids have shown potent antiprotozoal and antimicrobial activities. Conclusion: The Scrophularia genus seems to be a rich source of iridoids and terpenoids, but isolation and identification of its alkaloids have been a neglected area of scientific study. The diverse chemical compounds and biological activities of this genus will motivate further investigation on Scrophularia genus as a source of new therapeutic medications.